Reconhecimento e cuidado : cotidiano de docentes com condições crônicas de uma instituição de ensino tecnológico - Almeida, Karla Beatriz Barros de (2022)
ABSTRACT: This study aimed to analyze the recognition, based on the theoretical references of Axel Honneth and Christopher Dejours, and its relationship with care, according to Joan Tronto in the daily work and chronicity of teachers. Qualitatively, the socioanthropological perspective guided the study, through the experience approach, made possible by biographical research. From January to March 2021, biographical interviews were conducted with ten teaching staff from a technological and higher education institution in Mato Grosso. Data were performed through the use of the MAXQDA 2020 software and data analysis was based on content analysis. Considering the daily work of teachers with chronic conditions, relationships were woven between the meanings attributed by them to their work and the suffering resulting from the repercussions of the chronic condition itself, work and social relations of work that generate feelings of disrespect. The attribution of meanings to the teaching work proved fundamental in overcoming adverse situations, and the work was a source of pleasure and the teaching identity, and the notion of identity was based on the process of its social construction. The efforts to maintain the work spent even in the face of sharp ness of chronicity are justified by the constant search for the possibility of living a normality, opposing those sufferings. Therefore, it is necessary to identify teachers with the work they do and to recognize their work and/or their attributes and not about non-work. The chronic condition in its sharpening may compromise the construction of the social sense of work due to fragmentations such as absences and limitations imposed in the exercise of work. Disrespect, which is opposed to social recognition, can be relieved through recognition for the work done and the pleasure resulting from it. Pleasure at work may even be related to the softening of the repercussions of the chronic condition. The pandemic has changed the daily life of teachers, deflating repercussions on the chronic condition, which can be sharpened and have their care routine modified. It was noticed that the intensification and precariousness of teaching work were exacerbated, generating other circumstances that hinder the dynamics of recognition, increasing the possibility of triggering exacerbations of the chronic condition. Recognition, in any context, is the way to care, and a teaching institution can be a caregiver when revisiting the care offered and evaluating how it has had repercussions on the lives of chronicly ill teachers, supporting them within their potentialities.